Attribute-Based Access Control Frameworks for Granular Data Access in Cloud-Based Insurance Systems (Journal of Computational Intelligence and Robotics, 2021)
The rapid adoption of cloud-based infrastructure in the insurance sector has intensified the need for robust access control mechanisms to manage sensitive datasets securely. Traditional access control models, such as Role-Based Access Control (RBAC) and Mandatory Access Control (MAC), exhibit limitations in addressing the dynamic and granular access requirements of modern insurance platforms. Attribute-Based Access Control (ABAC), characterized by its reliance on attributes—user, object, environmental, and contextual—emerges as a highly adaptable framework for managing access to sensitive information while adhering to stringent regulatory standards such as the Health Insurance Portability and Accountability Act (HIPAA) and the General Data Protection Regulation (GDPR).This paper investigates the integration of ABAC frameworks into cloud-based insurance systems to enable fine-grained, dynamic, and policy-driven access management. The study begins by delineating the key challenges faced by insurance providers in securing sensitive datasets, particularly in a multi-tenant cloud environment. These challenges include mitigating insider threats, ensuring compliance with complex regulatory requirements, and providing scalable access mechanisms without compromising system performance.The core contribution of this research is a detailed analysis of ABAC's operational principles and its application in insurance platforms. The ABAC model evaluates access requests based on multi-dimensional attributes, providing unparalleled granularity in defining and enforcing access policies. For instance, policies can be formulated to grant access to medical records only to licensed professionals during working hours or to restrict sensitive customer information based on geographical regulations. Such capabilities surpass the rigidity of RBAC, which depends solely on predefined roles.The paper also explores the role of advanced technologies, such as machine learning and natural language processing, in enhancing ABAC frameworks. These technologies are pivotal in automating policy management, detecting anomalies, and adapting to evolving security threats. A case study involving a simulated insurance platform demonstrates how an ABAC-based system can enforce real-time, attribute-driven policies to manage access to claims data while maintaining regulatory compliance. This implementation showcases the potential of ABAC in reducing unauthorized access, improving operational efficiency, and mitigating risks associated with data breaches.To address implementation challenges, the paper provides a comprehensive discussion on the technical requirements and considerations for deploying ABAC in cloud-based environments. Key aspects include attribute classification and management, policy creation and lifecycle management, and performance optimization in high-traffic scenarios. The scalability of ABAC systems is evaluated, highlighting their capacity to handle large datasets and diverse user bases, which are intrinsic to insurance platforms.The research further evaluates the compatibility of ABAC with privacy-preserving technologies, such as homomorphic encryption and secure multi-party computation, to strengthen data protection in compliance with GDPR and HIPAA mandates. Additionally, the paper identifies potential barriers, such as the complexity of attribute definition, policy conflicts, and the computational overhead associated with dynamic policy enforcement. Solutions and best practices are proposed to mitigate these challenges, including the adoption of standardized policy languages like XACML and the integration of policy simulation tools to validate and optimize access policies before deployment.Future directions for research are explored, emphasizing the need for adaptive ABAC systems that leverage artificial intelligence to dynamically adjust policies based on contextual and behavioral analytics. The importance of interoperability among ABAC systems and other access control mechanisms is also underscored to ensure seamless integration across heterogeneous cloud environments. Furthermore, the study highlights the necessity of establishing a regulatory framework that explicitly acknowledges the role of ABAC in safeguarding sensitive data within the insurance sector.